School Collaboration Management and Parent Participation in Realizing Quality Schools in the Era of Independent Curriculum (Study at SD Negeri Klero 02) - Ihza Amrulloh; Choirun Nisa (Universitas Muhammadiyah Surakarta, 2025)
Purpose: This study aims to examine collaborative management between schools and parents in improving the quality of basic education at SD Negeri Klero 02, especially in the context of the independent curriculum. Methodology: The approach used was descriptive qualitative with data collection through observation, interviews, and documentation, involving school principals, teachers, and parents. Data triangulation techniques were applied to increase the validity of the findings.Results: Systematic and integrated collaboration management between schools and parents successfully supports active learning, character development, and improved academic achievement among students. Effective communication, firm yet humane leadership, and regular parental involvement were found to be key factors in creating a positive and inclusive learning environment. The role of the principal in facilitating open dialogue and managing conflicts transparently is very important.Applications/Originality/Value: This study emphasizes the importance of multi-stakeholder synergy in education as the foundation for the sustainable academic and personal development of students. These findings provide empirical contributions for policymakers and education practitioners in designing strategies to strengthen partnerships between schools and families and optimize the implementation of the independent curriculum. Thus, this study supports the improvement of student learning outcomes and character in a comprehensive manner in primary education.